Practical and general diels-alder reaction of pentafulvenes with arynes - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2012)
A high-yielding, versatile and practical Diels–Alder reaction of pentafulvenes with arynes under mild reaction conditions is reported. The aryne generated by the fluoride induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes efficient cycloaddition with 6-substituted and 6,6-disubstituted pentafulvenes leading to the formation of benzonorbornadiene derivatives.